Fatores limitantes do ensino-aprendizagem matemática em uma escola de educação básica: um relato de experiência docente - SOUZA, Almiro Alexandre Melo (2022)
The teaching of mathematics is not an easy task, teachers at all levels of education present a very similar picture in terms of the challenge of involving the student in the learning process, in addition to memorizing formulas. Thus, motivated by the question: What factors can be limiting the teaching of Mathematics with regard to trigonometry in a practical approach? This study aimed to expose results of a teaching experience in relation to the teaching and learning process of Mathematics, with regard to the practice of trigonometry. To this end, it aimed to develop educational activities to minimize limitations; and, link theoretical mathematics to everyday practice. The 9th grade class was selected, and participant observations were applied for two months. Students' simulations were analyzed during the research period, in order to consider their greatest difficulties in mathematics. In parallel to the investigation, a bibliographic collection on mathematical teaching and learning was consulted. The results were compiled, reaching the conclusion that the practical classes together with the theoretical classes end up causing a good development in the performance of the competence, the students' abilities helping in positive learning results. It was confirmed with this study, that there is a need for practices to be rethought in order to overcome challenges, whether they are external or internal to the school.